Pengembangan Bahan Ajar Berbasis Inkuiri Terbimbing Pada Materi Ikatan Kimia Untuk Siswa Kelas X - Dewi, Bunga; Purba, Jamalum (Jurnal Pendidikan Indonesia, 2022)
This study aims to determine the feasibility of presenting Guided Inquiry-Based Teaching Materials in accordance with BSNP standards, which include: (1) Content Feasibility, (2) Presentation Feasibility, (3) Language Feasibility, and (4) Graphical Feasibility. knowing the students’ responses to guided inquiry-based teaching materials on ionic bonds and covalent bonds. This research was developed using the Research & Development (R&D) method using a development model in the form of ADDIE. This research was conducted at the State University of Medan (UNIMED) and SMA Negeri 1 Sunggal, the teaching materials were validated by a Chemistry Lecturer, Chemistry teacher, and the responses of 20 students of SMA class X MIPA. The instrument used is a questionnaire according to BSNP standards. The results of this study indicate that through the development of Guided Inquiry-Based Teaching Materials on Chemical Bonding Materials for Class X High School Students: (1) Average Feasibility of Content by Lecturers is 3.58 and by Teachers 3.44., (2) Average Eligibility Presentation by Lecturer 3.73 and by Teacher 3.53., (3) Average Feasibility of Language by Lecturer 3.77 and by Teacher 3.58., (4) Average Feasibility of Graphics by Lecturer 3.75 and by Lecturer Teacher 3.55. And the average result of student responses is 3.70. This means that the teaching materials that have been developed are feasible and do not need to be revised